Konsep dan Perbedaan IPS dengan Ilmu Sosial - Noviyanti, Tya; Sirait, Yuken Novi Yanti Br; Chan, Faizal; Noviyanti, Silvina (Lembaga Yasin AlSys, 2024)
This research aims to form concepts and differences between social studies and social sciences for prospective teachers. The method used is Systematic Literature Review (SLR) which prioritizes the relevance of the topic of previous articles as the basis for data collection. Data analysis was carried out using interactive data analysis techniques. The research results show that social studies teachers are most likely to understand social studies concepts during the learning period if the social studies learning system can prioritize emphasis on integrated concepts and follow existing traditions in social research. Discussion as a democratic step must be emphasized to help students realize the importance of social studies learning, so that the resulting understanding is not only normative but also considered important. Understanding is built on the desire to ask and know, not on one-way information given by teachers or textbooks. It is time for the social studies field to become more open and democratic by training teachers who understand the concepts and differences between social studies and social sciences, as well as supporting the continued development of national human resources.